Composition, properties of Ahnfeltia biochar and the possibility of its use as a fertilizer for Luvic Anthrosols or for hydroponics - Anastasia, Brikmans; Olga, Nesterova; Mariia, Bovsun; Alina, Kozlova; Tatyana, Karpenko; Andrei, Egorin (Edelweiss Applied Science and Technology, 2024)
Recycling of beach macrophytes into biochar may be a good ecological solution for beaches where macrophyte management strategies are absent or irrational. Currently, large amounts of Ahnfeltia accumulate on some beaches in Primorsky Territory. The potential of recycling Ahnfeltia beach sediments in Primorsky Territory by pyrolysis for use as a fertilizer was assessed. Ahnfeltia biochar had a pH of 8.0±0.5, P2O5 was 365±12 mg/100 g, K2O was 892±45 mg/100 g, and nitrogen was 8-10%. The water-holding capacity for the natural fraction was 432.5%, and for the fraction larger than 1 mm 630.4%. Ahnfeltia biochar had a higher value of water-holding capacity, plant nutrient content compared to wood biochar (Betula alba), which showed good results in Luvic Anthrosols (reduced CO2 emissions, increased yield). Thus, we assumed that Ahnfeltia biochar can show a good effect on Luvic Anthrosols, as well as on soils with similar properties. It was shown that Ahnfeltia biochar actively saturates an aqueous solution with P2O5 and can maintain a stable concentration of P2O5 for three weeks when growing lettuce. This shows that Ahnfeltia biochar has the potential to be used in hydroponic installations as a fertilizer.